Measuring financial inclusion in the MENA region: Comparative analysis - Rabab Jaber Chehayeb (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of this paper is to develop a new multidimensional financial inclusion index to measure the financial inclusion level for each of the 13 selected countries of the Middle East and North Africa region for the period 2004-2020. In addition, the comparative analysis approach encompasses the evolvement of financial inclusion for each country in the time period studied. Design/methodology/approach: This study builds onto Sarma's (2012) approach for measuring financial inclusion by forming a new and improved model including the depth dimension and new variables. The computed values are based on data on financial inclusion extracted from the World Bank and the International Monetary Fund, the Financial Access Survey database. Findings: The values of the new financial inclusion index reveal the inadequate efforts made by these countries to enhance financial inclusion as a way to improve the economic /income growth in the region. Research limitations/implications: This study has two limitations. The unavailability of data for some financial indicators made it inevitable to be included in the study, such as the digital banking. Such data is considered crucial for future studies on financial inclusion indexes. The other limitation is that some countries in the Middle East and North Africa region were excluded from this research due to the lack of data on some of the variables included in constructing and measuring the new index. Despite these limitation, policy-makers and central banks can benefit from this study to enhance financial inclusion practices in pursuit of economic /income growth. Originality/value: This study attempts to develop a new multidimensional index to measuring financial inclusion by including a new dimension/variables and analyzing the values.
Keywords: 650; Financial depth dimension; Financial inclusion; Financial inclusion index; Middle East and North Africa